Practice influencing formation and learning in Professional and Technological Education (Research, Society and Development, 2021)
The relationship between theory and practice characterizes and defines pedagogical actions that make it possible to better understand the teaching and learning process. Through this work, we tried to find answers that establish reflective analyzes about the factors that guide the teaching understanding about pedagogical action and the benefits that practical activities develop in learning. That said, a proposal was made to clarify the academic bias, with the intention of investigating the practical activities developed in Professional and Technological Education. In addition, theory and practice were articulated in the teaching and learning process, in order to mobilize the critical knowledge necessary for personal and professional training. In this context, we sought to reflect on whether practical activities, in Professional and Technological Education, play a practice based on theory. In addition, the importance of theory in relation to practice in the teaching and learning process was verified and the variables and conditions that guide the pedagogical practice of teachers in the application of practical activities were identified. This article is part of the results of our master's research and is based on a methodological approach based on a bibliographic research, supported by a qualitative investigation, which explores and reflects on the pedagogical practice in Professional and Technological Education. In this way, some reflections on the analyzed aspects of this theme are synthesized, according to the thinking of authors, such as Barato (2002, 2008, and 2011), Saviani (2007), Gamboa (2010), Pimenta (2009), Silva (2013), Guimarães (2014), among others, and some practical activities carried out at IFCE Campus Baturité are presented. As a result, this work contributes to the implementation of dynamic classes, which make it possible, in addition to the debates and discussions in the classroom, to carry out activities that contextualize learning, both in academia and in the labor market. Thus, it was concluded that the practical experiences carried out in several courses of the Federal Institute of Education, Science and Technology of the State of Ceará, Campus Baturité, substantiate the work and confirm the importance of the relationship between theory and practice in the teaching and learning process.